(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Powder juices are widely used by the people in the study area because its low price compared to fresh juices. These powder juices may contain some radioactive materials. The study aimed to measure radioactivity concentrations of Radium and Uranium in the most used kinds of powder juice samples, selected from Iraq markets. CR-39 detector with sealed can technique, used to measure the radioactive elements concentrations. The radionuclides observed in the present work are, the estimated radon activity concentration range is between 57.146-151.129 Bq/m3 with a mean value of 107.62 Bq/m3. The radon concentration mean value is within of 100 Bq/m3 the limits of (WHO) World Health Organization reference level, below of (NRPB) UK National Radiation Protection Board, and below of 200 Bq/m3 the European Commission Recommendation Level. The annual effective dose of radon varied between 1.441-3.813 mSv/y, are within the (UNSCEAR) range 0.2-10 mSv/y. Radium contents were found to vary between 0.188-0.498 Bq/kg and a mean value of 0.354 Bq/kg. The radium effective annual dose ranged between 1.050-2.779 μSv/y. The concentrations of uranium are in the range between 0.150-0.398 ppm with men value of 0.283 ppm. The effective annual dose of uranium varied between 1.669-4.414 μSv/y. This work helped in identifying and measuring the specified activity of radionuclide present in powdered fruit juices consuming in Iraq and showed that these kinds of powder juice are safe for consumption.